Advanced Glycation End Products: New Clinical and Molecular Perspectives (2021)
Diabetes mellitus (DM) is considered one of the most massive epidemics of the twenty-first century due to its high mortality rates caused mainly due to its complications; therefore, the early identification of such complications becomes a race against time to establish a prompt diagnosis. The research of complications of DM over the years has allowed the development of numerous alternatives for diagnosis. Among these emerge the quantification of advanced glycation end products (AGEs) given their increased levels due to chronic hyperglycemia, while also being related to the induction of different stress-associated cellular responses and proinflammatory mechanisms involved in the progression of chronic complications of DM. Additionally, the investigation for more valuable and safe techniques has led to developing a newer, noninvasive, and effective tool, termed skin fluorescence (SAF). Hence, this study aimed to establish an update about the molecular mechanisms induced by AGEs during the evolution of chronic complications of DM and describe the newer measurement techniques available, highlighting SAF as a possible tool to measure the risk of developing DM chronic complications.